Current antiviral practice and course of Hepatitis B virus infection in inflammatory arthritis: a multicentric observational study (A - DİRESKENELİ, RAFİ HANER (AVES, 2015)
Objective: The reactivation of hepatitis B virus (HBV) infection is a well-known event in hepatitis B surface antigen (HbsAg)-positive patients receiving immunosuppressive therapy. The objective of this study was to assess the antiviral practice and course of HBV infection in inflammatory arthritis. Material and Methods: Nineteen rheumatology centers participated in this retrospective study. HbsAg-positive patients who were taking disease-modifying antirheumatic drugs and who were being tested for HBV viral load at a minimum of two different time points were included. The case report form (CRF) consisted of demographic data, rheumatic diseases, treatment profiles, transaminase levels, viral hepatitis serological markers, and HBV viral load. The reactivation of HBV was defined as the abrupt rise in HBV replication by an increase in serum HBV DNA levels in a patient with a previously inactive HBV infection. Results: In total, the data of 101 (female 50.5%) patients were included (76 patients with inactive HBV carriers and 25 patients with chronic HBV infection). The mean age of patients was 44 +/- 12 years, and the mean follow-up duration was 31 +/- 22 months. Of the 101 patients, 70 (69.3%) received antiviral treatment. HBV reactivation was detected in 13 of 76 (17.1%) patients with inactive HBV carriers. HBV reactivation was observed less frequently, not although significantly, in those patients receiving antiviral prophylaxis compared with those not receiving prophylaxis [5/41 (12.2%) vs. 8/33 (24.2%), p=0.17]. Forty-two patients (31 patients had inactive HBV carriers) were using anti-tumor necrosis factor agents. HBV reactivation was detected in 6 of the 31 (19.3%) patients. Twenty-five patients had chronic hepatitis, and five (20%) of them had not received antiviral prophylaxis. HBV viral loads were persistently elevated in 7 (28%) of 25 patients (three patients under and four patients not under antiviral treatment). Conclusion: HBV reactivation was observed in approximately 17% of patients under immunosuppressive treatments. HBV reactivation was more frequently observed in those who did not receive antiviral prophylaxis.
Keywords: Rheumatoid arthritis; ankylosing spondylitis; hepatitis B infection; hepatitis B reactivation; hepatitis B viral load; REACTIVATION; LAMIVUDINE; CHEMOTHERAPY